Non-Profit Organizations TF Risk Assessment Tool : Identifying the FATF NPOs at Risk of Terrorist Financing Abuse - Guidance Manual - World Bank (Washington, DC, 2022)
The National Money Laundering/Terrorist Financing Risk Assessment (NRA) Toolkit has been developed by World Bank Group (WBG) staff members to support WBG client countries and jurisdictions in self-assessing their money laundering and terrorist financing risks.The nonprofit organization (NPO) tool of the NRA Tool serves as an instrument that jurisdictions can use to support their analyses of the terrorist financing abuse of NPOs. Through it, the Working Group will identify NPOs that meet the Financial Action Task Force (FATF) definition, assess the evidence of NPO abuse for terrorist financing, determine the inherent risk (exposure to active terrorist threat), and review the quality of existing mitigation measures. This analysis should seek to complement and draw on national terrorism and terrorist financing risk assessments.